2021
DOI: 10.3389/fncel.2021.672136
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Changes in BDNF Expression in MK-801-Induced Hippocampal Astrocytes Through NMDAR/PI3K/ERK Signaling

Abstract: Dizocilpine (MK-801), a non-competitive N-methyl-D-aspartic acid receptor (NMDA-R) antagonist, can induce schizophrenia-like symptoms in healthy individuals, implicating NMDA-R hypofunction in disease pathogenesis. Brain-derived neurotrophic factor (BDNF) is also implicated in schizophrenia, and expression is regulated by NMDA-R activity, suggesting a functional link. We previously found that BDNF signaling was upregulated by MK-801 in cultured hippocampal astrocytes, but the underlying mechanism is not clear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
2
0
2
Order By: Relevance
“…One might expect that the plasma membrane expression of NHE5 should be low in schizophrenia with hypofunction of NMDA receptors and BDNF levels should be elevated. There are clinical and experimental reports that ketamine or MK-801 elevates BDNF and TrkB levels [120][121][122]. However, the elevation was transient and did not last.…”
Section: Nhe5mentioning
confidence: 99%
“…One might expect that the plasma membrane expression of NHE5 should be low in schizophrenia with hypofunction of NMDA receptors and BDNF levels should be elevated. There are clinical and experimental reports that ketamine or MK-801 elevates BDNF and TrkB levels [120][121][122]. However, the elevation was transient and did not last.…”
Section: Nhe5mentioning
confidence: 99%
“…However, previous studies have shown rather contrary results in terms of the BDNF levels after MK-801 treatment. Regarding the role of BDNF in memory/learning processes, MK-801 is expected to diminish the BDNF levels, and in some studies, it does, mainly in the hippocampus [ 127 , 128 ], but other studies have reported upregulated levels, including in vitro studies [ 129 , 130 ], which may suggest a response to the toxic action of MK-801 and/or action of compensatory mechanisms.…”
Section: Pharmacological Modelsmentioning
confidence: 99%
“…Ensaios biológicos usando animais ou culturas celulares como modelos ainda estão surgindo, com o objetivo de fornecer mais informações sobre os efeitos induzidos pela administração de neuromoduladores e drogas antipsicóticas (GÜNERI; SCHEEL-KRÜGER; LUO, 2021; PEREZ-RANDO et al, 2017;WANG et al, 2019;YU et al, 2021).…”
Section: Modelos Experimentais De Esquizofreniaunclassified
“…O composto MK-801 possui uma afinidade, seletividade e potência inibitória maior do que a cetamina e a fenciclidina (WALLACH et al, 2016;YU et al, 2015), portanto, esse composto é amplamente empregado em modelos animais para induzir alterações comportamentais e neuroquímicas relacionadas à esquizofrenia. Ele pertence à classe das aminas secundárias e atua como antagonista não competitivo de receptor NMDA, não apenas em neurônios, mas também em células da glia (BRANDÃO-TELES et al, 2017;YU et al, 2015YU et al, , 2021. Em roedores, nos efeitos comportamentais induzidos pelo MK-801 estão incluídos prejuízo no aprendizado espacial e na memória (SAWAHATA et al, 2021;XIAO et al, 2019), sociabilidade reduzida (BIAŁOŃ et al, 2021;PERDIKARIS;DERMON, 2022;XIAO et al, 2019), hipolocomoção (SANTILLÁN-URQUIZA et al, 2019) ou hiperlocomoção (KRAEUTER et al, 2020;XIAO et al, 2019) e perturbações de condicionamento de medo (BIAŁOŃ et al, 2021;ZHAN et al, 2021) 2015).…”
Section: Modelos Experimentais De Esquizofreniaunclassified